Remarkable synergistic effects of Mg2NiH4 and transition metal carbides (TiC, ZrC, WC) on enhancing the hydrogen storage properties of MgH2. (28th February 2020) - Yao, Linglong; Lyu, Xuanyu; Zhang, Jiguang; Liu, Yana; Zhu, Yunfeng; Lin, Huaijun; Zhang, Yao; Li, Liquan
Abstract: Nanostructuring and catalyzing are effective methods for improving the hydrogen storage properties of MgH2 . In this work, transition-metal-carbides (TiC, ZrC and WC) are introduced into Mg–Ni alloy to enhance its hydrogen storage performance. 5 wt% transition-metal-carbide containing Mg95 Ni5 (atomic ratio) nanocomposites are prepared by mechanical milling pretreatment followed by hydriding combustion synthesis and mechanical milling process, and the synergetic enhancement effects of Mg2 NiH4 and transition-metal-carbides are investigated systematically. Due to the inductive effect of Mg2 NiH4 and charge transfer effect between Mg/MgH2 and transition-metal-carbides, Mg95 Ni5 -5 wt.% transition-metal-carbide samples all exhibit excellent hydrogen storage kinetic at moderate temperature and start to release hydrogen around 216 °C. Among them, 2.5 wt% H2 (220 °C) and 4.7 wt% H2 (250 °C) can be released from the Mg95 Ni5 -5 wt.% TiC sample within 1800 s. The unique mosaic structure endows the Mg95 Ni5 -5 wt.% TiC with excellent structural stability, thus can reach 95% of saturated hydrogen capacity within 120 s even after 10 cycles of de-/hydrogenation at 275 °C. And the probable synergistic enhancement mechanism for hydrogenation and dehydrogenation is proposed. Graphical abstract: Image 1 Highlights: TiC, ZrC, WC were employed to improve the hydrogen storage properties of Mg95 Ni5 . Charge transfer effect between Mg/MgH2 and TMCs facilitates the dehydrogenation. Synergetic effects of Mg2 NiH4 and TMCs were investigated in depth. HCS + MM-Mg95 Ni5 -5 wt.% TiC composite exhibits excellent cycle stability.